Tensor Force Effect on Shape Coexistence of N = 28 Neutron-Rich Isotones - 王艳召 顾建中 于国梁 侯召宇 (Chinese physics letters, 2014)
The tensor force effect on potential energy surfaces of the N = 28 neutron-rich isotones is investigated by using the deformed Skyrme Hartree-Fock-Bogoliubov approach with the T22 interaction. It is found that, without the tensor force, ^40Mg and ^46At have prolate and spherical ground states, respectively. The ground states of ^42Si and ^44S are oblate. The shape coexistence in ^40Mg, ^42Si and ^44S is evident. However, the ground state deformations of these isotones are not changed and the shape coexistence in ^42Si and ^44S vanishes when the tensor force is switched on. Taking ^42Si as an example, the disappearance of the shape coexistence is understood by analyzing the tensor force effect on the shell correction energies.